A platelet–endothelium interaction mediated by lectin-like oxidized low-density lipoprotein receptor-1 - Kakutani, Makoto (The National Academy of Sciences, 2000)
One crucial role of endothelium is to keep the innermost surface of a blood vessel antithrombotic. However, the endothelium also expresses prothrombotic molecules in response to various stimuli. The balance between the antithrombotic and prothrombotic nature of the endothelium is lost under certain conditions. During atherosclerosis, the attachment of platelets to the vessel surface has been suggested to promote the proliferation of smooth muscle cells and intimal thickening as well as to affect the prognosis of the disease directly through myocardial infarction and stroke. Dysfunctional endothelium, which is often a result of the action of oxidized low-density lipoprotein (OxLDL), tends to be more procoagulant and adhesive to platelets. Herein, we sought the possibility that the endothelial lectin-like OxLDL receptor-1 (LOX-1) is involved in the platelet–endothelium interaction and hence directly in endothelial dysfunction. LOX-1 indeed worked as an adhesion molecule for platelets. The binding of platelets was inhibited by a phosphatidylserine-binding protein, annexin V, and enhanced by agonists for platelets. These results suggest that negative phospholipids exposed on activation on the surface of platelets are the epitopes for LOX-1. Notably, the binding of platelets to LOX-1 enhanced the release of endothelin-1 from endothelial cells, supporting the induction of endothelial dysfunction, which would, in turn, promote the atherogenic process. LOX-1 may initiate and promote atherosclerosis, binding not only OxLDL but also platelets.